Reflex of urban space changes and climate conditions in Biomphalaria glabrata population dynamics on potential schistosomiasis foci in northeastern Brazil - Oliveira, Daniel Santos Oliveira Santos; Calasans, Taíssa Alice Soledade; Melo, Andrea Gomes Santana; Melo, Claudia Moura; Madi, Rubens Riscala; Jeraldo, Verónica Lourdes Sierpe (Scientia Plena, 2016)
To understand better the space-disease process of urban schistosomiasis mansoni in northeastern Brazil, this study assessed four sites considered to be potential foci. Molluscs were collected monthly between January to December 2010, were assessed for species and infection, quantified, and measured; rainfall data were obtained; and water samples were analysed for faecal coliform. The specimens collected were identified as Biomphalaria glabrata. At all sites, we observed high levels of faecal coliforms. The sanitation projects within the Coqueiral and Japãozinho neighbourhoods positively influenced population of B. glabrata. A similar phenomenon occurred in the Soledade neighbourhood, where a portion of the study site was excavated for building construction. The population of molluscs and positivity increased during the rainy season whereas mmolluscs size was differently influenced by rainfall. Rainfall combined with anthropogenic activity influenced foci dynamics during the study period, indicating that schistosomiasis is well-established in the Aracaju urban environment, primarily due to the ability of Biomphalaria to adapt to manmade changes associated with precarious sanitation.